How to schedule the Volleyball Nations League - Lambers, R.; Rothuizen, L.; Spieksma, F. C. R. (Journal of Sports Analytics, 2023)
The Volleyball Nations League is the elite annual international competition within volleyball, with the sixteen best nations per gender contesting the trophy in a tournament that spans over 6 weeks. The first five weeks contain a single round robin tournament, where matches are played in different venues across the globe. As a consequence, each team follows an intensive travel plan, where it happens quite often that there is a large discrepancy between travel burdens of opposing teams. This is considered a disadvantage for the team that travelled more. We analyse this problem, and find that it is closely related to the well-known Social Golfer Problem: we name the resulting problem the Traveling Social Golfer Problem (TSGP). We propose a decomposition approach for the TSGP, leading to the so-called Venue Assignment Problem and the Nation Assignment Problem. We prove that a solution to the Venue Assignment problem determines the amount of unfairness, and we also prove that any solution of the Venue Assignment problem can be extended to a solution to the Nation Assignment problem satisfying the so-called home-venue property. Using integer programming methods, we find, for real-life instances, the fairest schedules with respect to the difference in travel distance.